Comparing economic theories or: Pluralism in economics and the need for a comparative approach to scientific research programmes - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2020)
Pluralism in economics appears to be a double-edged sword: we need more than one theory to grasp and explain the entire economic world, yet a plurality of possible explanations undermines the aspiration of the economic discipline to provide 'objective knowledge' in the singular of the 'one world one truth' conception. Therefore, pluralism is often equated with relativism and obscurantism. In this article, I will explore both the demand for pluralism and the fear of relativism and obscurantism, scrutinising each position in order to evaluate their respective justification and devising a methodological proposal that may appease both the defender and the sceptic of economic pluralism.
Keywords: A11; B40; B50; E11; E12; E13; 330; Pluralism; Methodology; Paradigm